Inpatient Antibiotic Costs Associated With Switching From Vancomycin to Daptomycin for Outpatient Parenteral Antibiotic Therapy. (February 2022) - Beardsley, James; Patel, Swetangini; Cook, Corbin; Pierce, Brandi; Johnson, James; Ohl, Christopher; Luther, Vera
Purpose: The common practice of changing patients to daptomycin for outpatient parenteral antibiotic therapy (OPAT) can increase inpatient daptomycin use and impact inpatient pharmacy expenses. The purpose of this study was to quantify the additional inpatient antibiotic expenditures associated with changing patients from vancomycin to daptomycin for OPAT.Methods: This study examined patients who were discharged from January 1, 2018 to June 30, 2019. Patients were included if they were ≥18 years old, transitioned from vancomycin to daptomycin prior to discharge, and were cared for by the Infectious Diseases OPAT program. Patients switched to daptomycin for therapeutic reasons were excluded. A cost analysis evaluating the vancomycin regimen prior to changing to daptomycin and the daptomycin doses given prior to discharge and during readmissions for the first 6 weeks after discharge was performed using Wholesale Acquisition Costs. The primary outcome was the inpatient antibiotic expense associated with changing to daptomycin for OPAT.Results: Sixty-eight patients met study criteria. The mean number of inpatient doses of daptomycin administered prior to discharge was 4.3. Twelve patients were readmitted and received a mean of 5.3 additional doses. The estimated cost difference between the inpatient daptomycin doses and equivalent vancomycin therapy was $2647 per patient. Limiting patients to only 1 pre-discharge dose of daptomycin would reduce this cost difference to $926 per patient.Conclusion: Switching from vancomycin to daptomycin for OPAT can be associated with substantial inpatient pharmacy costs. These excessive costs can be mitigated if only 1 dose of daptomycin is given before discharge.